Possibilities of the Development of Social Competence With Drama Pedagogy Methods in (Remedial) Pedagogy Work (Training and Practice : Journal of Educational Sciences, 2017)
The change of social and professional approach has required the reform of the care of the children’s population requiring special care. The education, training and helping of children demanding advanced attention do not only require pedagoguess and helping experts having complex skills, but also a task performance based on cooperation.The social behaviour forms, social abilities and capabilities play an important role in every area of life, so in the kindergarten and school life as well. The inappropriate development of social competence can be a problem in integration, in the establishment of relations with associates, grown-ups or in the appropriate performance.In our research we wanted to confirm that the application of drama play asa drama pedagogy method exercises favourable effect on the development of social competence, it helps in the establishment of social relations, further it increases the performance level and the efficiency of learning abilities.